The TanDEM-X Mission Phases - Ten Years of Bistatic Acquisition and Formation Planning - Bachmann, Markus; Kraus, Thomas; Bojarski, Allan; Schandri, Maximilian; Boer, Johannes; Busche, Thomas; Bueso Bello, Jose-Luis; Grigorov, Christo; Steinbrecher, Ulrich; Buckreuss, Stefan; Krieger, Gerhard; Zink, Manfred (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2021)
TanDEM-X is a formation flying interferometer consisting of two SAR satellites. Together they acquire bistatic SAR data of the earth in order to generate a global digital elevation model as well as individual scientific interferometric datasets on user request. This article gives an overview about ten years of acquisition and formation planning for the TanDEM-X mission. This planning on the one hand includes the derivation of the formation, i.e., the 3-D distance between both satellites in orbit. On the other hand, it needs to consider the regions of interest and the mission, satellite, and instrument constraints in order to effectively plan the bistatic acquisitions. During the ten years in operation TanDEM-X successfully completed various mission goals during dedicated mission phases. All these phases, their characteristics as well as the scientific and commercial outcome are described in detail.
Created from Fastlane, Scopus look-up
Keywords: Acquisition planning; digital elevation model (DEM); formation; global DEM; mission phases; TanDEM-X